Ligand-enabled ruthenium-catalyzed meta-C−H alkylation of (hetero)aromatic carboxylic acids - Luo, Xianglin; Hou, Peichao; Shen, Jiayi; Kuang, Yifeng; Sun, Fengchao; Jiang, Huanfeng; Gooßen, Lukas J.; Huang, Liangbin (Nature communications, 2024)
Carboxylates are ideal directing groups because they are widely available, readily cleavable and excellent linchpins for diverse follow-up reactions. However, their use in meta -selective C−H functionalizations remains a substantial unmet catalytic challenge. Herein, we report the ruthenium-catalyzed meta -C–H alkylation of aromatic carboxylic acids with various functionalized alkyl halides. A bidentate N -ligand increases the electron density at the metal center of ortho -benzoate ruthenacycles to the extent that single-electron reductions of alkyl halides can take place. The subsequent addition of alkyl radicals is exclusively directed to the position para to the C Ar –Ru bond, i.e., meta to the carboxylate group. The resulting catalytic meta -C−H alkylation extends to a wide range of (hetero)aromatic carboxylic acids including benzofused five-membered ring heteroarenes but no pyridine derivatives in combination with secondary/tertiary alkyl halides, including fluorinated derivatives. It also allows site-selective C5−H alkylation of 1-naphthoic acids. The products are shown to be synthetic hubs en route to meta -alkylated aryl ketones, nitriles, amides, esters and other functionalized products. Carboxylates are ideal directing groups for aryl C–H functionalizations, given their wide availability and relative ease of functional group interconversion; however, their potential in meta-selective functionalizations has not been fully realized. Here, the authors use carboxylates for meta-selective alkylations via ruthenium catalysis.